Tax Compliance Reporting: Antecedent and Moderating Effect - Zaki Fakhroni; Lela Lela Istyana Nur Fitraratri (Journal of Accounting and Taxation, 2022)
To make it easier for taxpayers to report their taxes, the Balikpapan city government provides facilities in the form of an online tax reporting application called E-SPTPD. To reduce fraud in tax reporting, the government has also installed transaction recording tools in restaurants in Balikpapan City. The purpose of this study was to obtain empirical evidence of a relationship between the use of E-SPTPD on tax reporting compliance with the antecedent factors of information technology readiness and transaction recording tools as moderators. This type of research is quantitative research using primary data and for the sample using quota sampling method with a total of 57 respondents. Data analysis using SEM-PLS assisted by SmartPLS Version 3. The results of this study obtained empirical evidence that: (1) readiness of information technology has a positive and significant effect on the use of E-SPTPD: (2) the use of E-SPTPD E-SPTPD has a positive and significant effect on tax reporting compliance: (3) transaction recording tools cannot moderate the relationship between the use of E-SPTPD and tax reporting compliance. This study also produces new findings, namely there is an antecedent effect of information technology readiness which has a considerable influence before using E-SPTPD.